2015
DOI: 10.1586/17474086.2015.1060576
|View full text |Cite
|
Sign up to set email alerts
|

Tackling antibiotic resistance in febrile neutropenia: current challenges with and recommendations for managing infections with resistant Gram-negative organisms

Abstract: Multidrug resistant (MDR) Gram-negative bacteria (GNB) have emerged as important pathogens and a serious challenge in the management of neutropenic patients worldwide. The great majority of infections are caused by the Enterobacteriaceae (especially Escherichia coli and Klebsiella spp.) and Pseudomonas aeruginosa, and less frequently Acinetobacter spp. and Stenotrophomonas maltophilia. A broader-spectrum empiric antibiotic regimen is usually recommended in patients with a history of prior bloodstream infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 82 publications
1
10
0
2
Order By: Relevance
“…An earlier study in Uganda also found that of the patients who sought treatment at private clinics within 1 week of onset of symptoms, only 7% of them were properly managed. [16][17][18][19][20][21][22] Similar findings have been documented in Ghana where a high proportion, 70% of the respondents, practiced self-medication, and the most common antibiotic used was amoxicillin. 23 It is noted that the majority of drug shops (53.3%), were injecting patients probably with gentamicin and penicillin, to treat other bacterial infections like skin infections and urethritis or urinary tract infections.…”
Section: Discussionsupporting
confidence: 77%
“…An earlier study in Uganda also found that of the patients who sought treatment at private clinics within 1 week of onset of symptoms, only 7% of them were properly managed. [16][17][18][19][20][21][22] Similar findings have been documented in Ghana where a high proportion, 70% of the respondents, practiced self-medication, and the most common antibiotic used was amoxicillin. 23 It is noted that the majority of drug shops (53.3%), were injecting patients probably with gentamicin and penicillin, to treat other bacterial infections like skin infections and urethritis or urinary tract infections.…”
Section: Discussionsupporting
confidence: 77%
“…Broad spectrum antibiotics given as treatment or prophylaxis exert selection pressure leading to the survival of resistant strains of bacteria, particularly in the gut. 36 Some of the limitations of this study were as follows: (1) Speciation of microbial isolates could not be performed as conventional methods of microbial identification were used. (2) Anaerobic blood culture was not done owing to infrastructure-related issues.…”
Section: Discussionmentioning
confidence: 99%
“…Broad spectrum antibiotics given as treatment or prophylaxis exert selection pressure leading to the survival of resistant strains of bacteria, particularly in the gut. 36 …”
Section: Discussionmentioning
confidence: 99%
“…These pathogens are usually endogenous. Broad spectrum antibiotics given as treatment or prophylaxis exert selection pressure leading to the survival of resistant strains of bacteria, particularly in the gut [17]. Nouer et al described how patients with haematological malignancies undergo repeated cycles of chemotherapy and receive broad spectrum antibiotics with each cycle, which provides a suitable environment for selection pressure [17].…”
Section: Discussionmentioning
confidence: 99%